The important of compative fiqh in contemporary issue / Nursyahida Mohd Ali … [et al.] - Mohd Ali, Nursyahida; Azhan, Siti Khairul Aisyah; Mohamed, Nur Shahida; Patul Muin, Fairuz Irdina; Azman, Norshahira (2023)
The Fiqh has been characterised as the distinctive quality that is behind the survival and permanence of Islam in line with the spirit of civilization, in spite of all the conditions, issues, and barriers that the Islamic nation faced during its inception. The Islamic jurisprudence (Fiqh) is divided into two parts, (usl al- fiqh) and (fur al- fiqh), which refer to the science of the methodology and the science of the actual rules or legal field, respectively. The meaning of the fiqh is thus "The knowledge of legal rules of Shari'ah which had derived from their specific source." Al-Fiqh al-Muqaran is a comparative analysis and assessment of the claims and evidence made by jurists by a person who neither belongs to a legal school nor adheres to its legal philosophy. The purpose of fiqh al muqaran is to get the strongest opinion based on the strongest arguments that are most compatible with the basis, soul and general principles of Sharia. (Mujaaini, 2016). In addition, it is comparative fiqh to know the opinions of the imams of the madhhab in various issues that are divided by its rulings, along with the evidences that are the basis, as well as the ways of instinbat ruling from the evidences presented. know the basics and qaidah which is used by every Imam of the madhhab in instinbat the ruling of his dalils which certainly does not deviate from the Quran and Sunnah. That way, it will be the one who truly respects all the hnams of the sect without distinguishing from each other, because the evidences presented in reality are not detached from the rule of ijtihad. Fiqh Muqaran, it is also very important to contemporary issues, therefore, there are many discussions on the topic of fiqh muqaran in this study.